Preventing Fatal Incidents in School and Youth Group Camps and Excursions Understanding the Unthinkable - Brookes, Andrew (International Explorations in Outdoor and Environmental Education,, 2018)
This book approaches the prevention of fatal incidents in outdoor education and related fields through detailed study of past tragedies. Although safety in many fields is built on accumulated lessons from past incidents, tragedies on school or youth group camps and excursions are so infrequent and so widely scattered that knowledge from previous incidents can elude those who would benefit. Nevertheless, the emergence of unlearned lessons from the past weighs heavily when those affected by a tragedy judge whether an incident should have been prevented. This book provides a foundation for a detailed and comprehensive understanding of fatality prevention in outdoor education, and in youth camps and excursions. It compiles, examines, and analyses information on fatal incidents that have occurred over many decades, involving many kinds of groups and endeavours, from around the globe. No previous work has attempted this task.